A Comparative Analysis of Mucus Immunomodulatory Properties from Seven Marine Gastropods from the Mediterranean Sea - Clementina Sansone; Cecilia Balestra; Luigi Pistelli; Angelo Del Mondo; David Osca; Christophe Brunet; Fabio Crocetta (Cells, 2022)
The treatment of inflammatory and immune-related diseases due to dysfunctioning of the immune system necessitates modulation of the immune response through immunomodulatory compounds. Marine environments are considered as a new frontier for health benefit product implementations. Marine biodiversity is still a low explored resource, despite it is expected to represent an important platform for chemical bioactive compounds. Within the phylum Mollusca, gastropods are known to synthetize mucus, the latter presenting relevant bioactive properties, e.g., related to immunomodulant molecules able to activate the innate and acquired immune system. This study proposes a bioprospecting of the immunomodulant activity of mucus isolated from seven common gastropod species from the Gulf of Naples (Mediterranean Sea). Results showed that not all mucus displayed a significant cytotoxic activity on the two human cancer cell lines A549 and A2058. On the other hand, the mucus from Bolinus brandaris was strongly bioactive and was therefore thoroughly investigated at cellular, molecular, and protein levels on the human monocytes U937 line. It can conclusively induce monocyte differentiation in vitro and significantly stimulate natural immunity response.